Determinan Nilai Perusahaan LQ45 Di Bursa Efek Indonesia - Purba, Pebisitona Mesajaya; Evinta , Lenny Leorina; Sumiok, Cristofer (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2023)
The purpose of this study is to examine the effect of profitability, liquidity, audit quality and firm size on firm value. The population in this study used LQ45 companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2022 period. Determination of samples using the purposive sampling method, so that as many as 27 companies were obtained with a total of 93 research samples. Data analysis using multiple linear regression testing. The results showed that liquidity positively affects firm value, audit quality positively affects firm value, while firm size negatively affects firm value and profitability does not affect firm value.